Polarized benzene rings can promote the interaction between CaM and the CaMBD region of nNOS - Wan, Wei; Wang, Nan (Frontiers in Molecular Neuroscience, 2024)
IntroductionThe neuronal nitric oxide synthase (nNOS) subtype of nitric oxide synthase (NOS) is an enzyme required for learning and memory. Overactivation of nNOS can lead to oxidative/nitrite stress, which is complicit in the pathophysiology of various neurological and psychiatric disorders. Previous studies have shown that calmodulin (CaM) forms complexes with Ca2+ and binds to the calmodulin-binding domain (CaMBD) of nNOS, thereby upregulating its catalytic activity in hippocampal neurons. To date, there has been no explanation for the non-covalent interactions in the CaMBD-CaM binding structure model of nNOS.MethodsIn this study, we aimed to investigate the intrinsic factors involved in the binding of CaM to NOS-CaMBD and designed interfering peptides based on the N0 peptide structure of the original nNOS-CaMBD sequence: N1 (obtained from the L734F mutation), N2 (obtained from the F731Y and F740Y mutations), and N3 (obtained from the F731L, V738L, and F740L mutations). We employed homology modeling to construct six CaM-peptide complex models, aiming to elucidate the roles of key amino acid residues within the N0 peptide in its interaction with CaM by means of molecular dynamics simulations. The effect of the peptides on the activation and release of NO by nNOS in neurons was assessed using murine primary neuronal cells.ResultsWhen measuring neuronal NO content, it was found that adding N2 and N3 to cultivated neurons significantly increased nNOS activity, leading to the increased NO production. We found that interfering peptides could stably bind to CaM. Among them, N2 and CaM exhibited the strongest binding ability, indicating that the polarized benzene ring significantly enhanced the binding between nNOS-CaMBD and CaM. Conversely, the binding ability between N0 and CaM was the weakest, as they exhibited the worst polar contact, weakest hydrogen bonding, and the lowest binding free energy. The simulation results also highlighted several important amino acid residues: The K76 of CaM plays an important role in polar contact and hydrogen bonding formation, the L734 residue suppressed model flexibility to a certain extent and had an adverse effect on the overall binding free energy of the model. These results, compared with the results of cellular NO content, a preliminary verification of the antagonistic competitive mechanism between CaM allosteric activation of nNOS and SUMOylation hyperactivation was performed.DiscussionIn summary, this study explored the ability and mode of action of key residues in nNOS-CaMBD on the binding of interfering peptides to CaM, thereby providing new structural perspectives for the activation of nNOS by CaM and recommendations for drug design targeting the specific inhibition of nNOS.